Bio-inspired novel hybrid vertical axis wind turbine / Ts. Dr. Ashwindran Naidu Sanderasagran and Dr. Azizuddin Abd Aziz - Sanderasagran, Ashwindran Naidu; Abd Aziz, Azizuddin (Universiti Teknologi MARA, Kedah, 2019)
Today several countries are investing their resources on the development of renewable energy, the focused sector of development in renewable energy is wind power generation. Energy harvested by the wind turbine are relative to wind speed potential regardless the type or configuration of wind turbine used. Design modification were done on wind turbine by engineers in order to adapt the wind speed of the desired geographical area. In Malaysia studies indicated that the average wind speed potential is 2.1 m/s dependent on season and geographical area, which is not adequate in harvesting energy in megawatt scale. Researches indicates that, drag driven wind turbines VAWTs are suitable in harvesting wind energy in low wind speed potential. The objective of this research is to present the aerodynamics performance of a novel bio-inspired hybrid drag driven wind turbine and with two sub objective; operational under low speed wind potential, and low manufacturing cost. In this research, the novel hybrid design were created by the hybridizations of three design elements inspired by nature; Albatross bird’s wing, Pitcher plant, and Tulip flower. The novel wind turbine were design based on the principals of VAWT’s design parameters, in order to maintain design’s practicality and performance. Ansys fluent were used to perform aerodynamic performance study on the design. The usefulness of this research is to broaden the knowledge and understanding of bio-mimicry design implementation and adaptation into wind energy harvesting machinery.